2011
DOI: 10.1186/1471-2474-12-75
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal ambulatory measurements of gait abnormality in dystrophin-deficient dogs

Abstract: BackgroundThis study aimed to measure the gait abnormalities in GRMD (Golden retriever muscular dystrophy) dogs during growth and disease progression using an ambulatory gait analyzer (3D-accelerometers) as a possible tool to assess the effects of a therapeutic intervention.MethodsSix healthy and twelve GRMD dogs were evaluated twice monthly, from the age of two to nine months. The evolution of each gait variable previously shown to be modified in control and dystrophin-deficient adults was assessed using two-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 17 publications
2
35
0
Order By: Relevance
“…Our results are in line with those reported by Marsh et al and Barthelemy et al [10], [11]. Barthelemy et al found that both stride length and stride speed were reduced by approximately 50% in 2 to 9-month-old affected dogs [11]. Marsh et al compared male affected dogs with female carrier dogs (age range: 17- to 40-month-old) and they also noticed an approximately 40% reduction of the stride speed in affected dogs [10].…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…Our results are in line with those reported by Marsh et al and Barthelemy et al [10], [11]. Barthelemy et al found that both stride length and stride speed were reduced by approximately 50% in 2 to 9-month-old affected dogs [11]. Marsh et al compared male affected dogs with female carrier dogs (age range: 17- to 40-month-old) and they also noticed an approximately 40% reduction of the stride speed in affected dogs [10].…”
Section: Discussionsupporting
confidence: 94%
“…Our results are in line with those reported by Marsh et al and Barthelemy et al [10], [11]. Barthelemy et al found that both stride length and stride speed were reduced by approximately 50% in 2 to 9-month-old affected dogs [11].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Results tended to parallel those achieved with composite clinical scores discussed above. A subsequent longitudinal study showed that gait changes could be identified in GRMD dogs as early as 2 months of age and then evolved with age (Barthélémy et al 2011). …”
Section: Biomarkers For Assessment Of the Natural History And Responsmentioning
confidence: 99%